Assessment of the effect of different forms of Inconel 625 alloy feedstock in Plasma Transferred Arc (PTA) additive manufacturing - Cardozo, Eloisa Pereira; Rios Contesse, Sergio Eduardo; Ganguly, Supriyo; D'Oliveira, Ana Sofia C. M. (My University, 2018)
Additive manufacturing (AM) is an emerging fabrication technology, which can offer a faster, versatile, flexible, easily customizable, and a cheaper production path, when compared to conventional manufacturing. There are different additive manufacturing techniques differentiated by the way of material is made available and melted in each layer. The Plasma Transferred Arc (PTA) is a promising AM technique became of its superior energy efficiency compared to laser-related processes. PTA allows to process materials both in powder and wire forms. Recent evidences suggested that the characteristics of the feedstock will impact the final microstructure and consequently the mechanical properties of the deposit. This work carried out a detailed analysis on effects of the feedstock form using PTA to build multilayers with wire and powder IN625 alloy. It considered the specific features of each feedstock for the processing and explored the relationship with the characteristics of the deposited multilayers. Powder plus arc and wire plus arc multilayers were analyzed using confocal microscopy, scanning electron microscopy, X-ray diffraction, and micro-hardness profile. It is shown that the microstructure and mechanical properties of a multilayer component are influenced on choice of the feedstock, mainly because of the differing parameters that will be required in their processing.
Keywords: additive manufacturing; ni alloy; powder; wire; pta